DESKRIPSI LITERASI DIGITAL PESERTA DIDIK DI SMA MUHAMMADIYAH 1 PONTIANAK - Estu Widya Lestari; Stepanus Sahala Sitompul; Erwina Oktavianty (Jurnal Inovasi Penelitian dan Pembelajaran Fisika, 2022)
This study aims to decribe the digital literacy profile of students at SMA Muhammadiyah 1 Pontianak. The form of research used is survey. The sample in this study was selected through a saturated sampling technique (all members of the population) totaling 100 students. The research instrument using a questionnaire consists of 22 statements, 4 aspects and 12 indicators. The results showed that the digital literacy skills of students in the attitude aspect of the attitude indicator towards online learning were 62%, the socio-emotional aspect of the indicator was 59% teamwork, network sharing 70%, ethics 73%, legal literacy 71% and self-preservation 82%. The technical aspects of cognition and discovery indicators are 78% each, 63% presentation. The cognitive aspect of the analysis indicator is 65%, evaluation is 72% and creativity is 74%. In general, the four aspects of digital literacy skills are categorized as quite good, except for the socio-emotional aspect of the team work indicator of 59% which is still quite lacking. The lack of ability in these indicators is caused by students having difficulty communicating with group friends in online learning.